2000
DOI: 10.1128/mcb.20.9.3116-3124.2000
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Nonsense Mutations in Cell Culture and Mice by Multimerized Suppressor tRNA Genes

Abstract: We demonstrate here the first experimental suppression of a premature termination codon in vivo by using an ochre suppressor tRNA acting in an intact mouse. Multicopy tRNA expression plasmids were directly injected into skeletal muscle and into the hearts of transgenic mice carrying a reporter gene with an ochre mutation. A strategy for modulation of suppressor efficiency, applicable to diverse systems and based on tandem multimerization of the tRNA gene, is developed. The product of suppression (chloramphenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 54 publications
(50 reference statements)
2
46
0
Order By: Relevance
“…The closest demonstration of function recovery was described for chloramphenicol acetyltransferase (CAT) carrying a nonsense mutation, whose expression by a multimerized sup-tRNA was observed in a transgenic mouse model. 25 The present study constitutes the first report of efficient nonsense suppression induced by a sup-tRNA in a human cancer-associated gene, with recovery of full-length and likely functional protein. Importantly, we have shown E-cadherin expression rescue by suppressor-tRNAthat B30% of sup-tRNA Arg -expressing cells recovered E-cadherin membranous expression.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The closest demonstration of function recovery was described for chloramphenicol acetyltransferase (CAT) carrying a nonsense mutation, whose expression by a multimerized sup-tRNA was observed in a transgenic mouse model. 25 The present study constitutes the first report of efficient nonsense suppression induced by a sup-tRNA in a human cancer-associated gene, with recovery of full-length and likely functional protein. Importantly, we have shown E-cadherin expression rescue by suppressor-tRNAthat B30% of sup-tRNA Arg -expressing cells recovered E-cadherin membranous expression.…”
Section: Resultsmentioning
confidence: 70%
“…Several studies demonstrated efficient nonsense suppression in mammalian models, although the recovery of functional proteins was rarely shown. 15,20,[22][23][24][25] In this work we wish to: (1) evaluate the potential impact of using nonsense suppression in HDGC; (2) determine the number of tRNAs necessary to treat nonsense mutation-carrying HDGC families; and (3) assess the possibility of recovering expression of a functional protein from an allele carrying a nonsense mutation described in HDGC using a sup-tRNA. To our knowledge, this is the first demonstration of functional recovery of a causative gene in cancer by cognate amino acid replacement with sup-tRNAs.…”
Section: Cdh1mentioning
confidence: 99%
“…In a mammalian cell, there are probably more than 150 tRNA species generated by at least 1,300 tRNA genes (Hatlen & Attardi, 1971;Söll, 1993)+ Thus, the identification of individual isoacceptors by Northern blot analysis can be an initial approach to study tRNA involvement in different cellular processes+ However, the use of this approach is limited by the tRNA secondary/ tertiary structures that make the hybridization efficiency of specific oligonucleotide probes unpredictable (Kumazawa et al+, 1992;Mir & Southern, 1999;Petyuk et al+, 1999)+ Here we show that a combination of oligodeoxynucleotides employed in the pre/hybridization reaction can reshape the tRNA structure and increase the sensitivity of specific detection of a suppressor tRNA derived from the human serine tRNA up to 220-fold+ By removing this hindrance to tRNA hybridization, this approach greatly improves the sensitivity of Northern blot analysis so that identification of individual tRNA isoacceptors expressed at low levels can be undertaken+ suppress premature stop codons (Buvoli et al+, 2000)+ To determine the expression of different multimerized suppressor tRNA constructs, we first tested the ability of two oligodeoxynucleotide probes (oligonucleotides U and a; Fig+ 2) to discriminate between the suppressor (tRNAsu ϩ ) and the endogenous serine tRNA (Fig+ 1)+ In a preliminary set of experiments designed to determine the optimal oligonucleotide hybridization conditions, we found that both oligonucleotides hybridized specifically but very poorly to the tRNAsu ϩ + In contrast, they hybridized efficiently to a DNA plasmid carrying the same gene (data not shown)+ Based on these results and the observation that oligonucleotide probes can invade tRNA hairpin structures if a short single-stranded sequence is available to initiate the strand-displacement process (Petyuk et al+, 1999), we next studied the ability of longer probes (U1, a1, and a2; Fig+ 2) to disrupt the secondary structure of the anticodon, maintaining at the same time specificity for the tRNAsu ϩ + Because the D arm is predicted to be the less stable tRNA structure (Fig+ 3;Crothers et al+, 1974), an oligonucleotide complementary to this region was used as a reference for hybridization efficiency (oligonucleotide D3; Fig+ 2)+ The results of this analysis performed on tRNAsu ϩ made in mammalian cells showed that although the efficiency of hybridization can be increased with longer probes derived from oligonucleotide a (up to ;26-fold using oligonucleotide a2), specificity was lost despite high stringent wash conditions (Fig+ 2)+ Oligonucleotide D3 hybridized to the tRNAsu ϩ much more efficiently than the rest of the oligonucleotides complementary to the anticodon loop, confirming that this region of the tRNA seems to be more available for hybridization (Kumazawa et al+, 1992;Mir & Southern, 1999)+ To get around this physical/chemical constraint, we next attempted to selectively disrupt the tRNAsu ϩ intramolecular base pairing as well as other stacking interactions responsible for the tRNA tertiary structure+ To this aim, we designed an array of oligodeoxynucleotides targeting different tRNAsu ϩ regions (Fig+ 3), and we tested their ability to ...…”
Section: Introductionmentioning
confidence: 99%
“…Properties of oligonucleotides used as unfolders and thermodynamic analysis of different tRNAsu ϩ regions+ Melting temperatures for the DNA/RNA hybrid duplexes were calculated as in Figure 2+ Each unfolder is depicted as a thick line along its tRNAsu ϩ target region+ ⌬G of the five serine tRNAsu ϩ arms was calculated using the mfold program, version 3 Zuker et al+, 1999)+ ployed, a 115-or 4-12-fold increase in association rate between ribozyme and RNA was reported with long (;900 nt) or short (39-452 nt) substrates, respectively (Jankowsky & Schwenzer, 1996)+ Here we show that the presence of 100-fold molar excess of cold unfolders over the tRNAsu ϩ increases the hybridization signal of an oligonucleotide complementary to the anticodon loop up to 220-fold+ Although FIGURE 4. Unfolder oligonucleotides enhance the hybridization efficiency of an oligonucleotide probe complementary to the tRNAsu ϩ anticodon loop+ Gray bars and black bars correspond, respectively, to the in vitro-transcribed tRNAsu ϩ or tRNAsu ϩ made in mammalian cells+ The gray thick lines along the tRNAsu ϩ correspond to the 59-end-labeled oligonucleotide a; the black thick lines correspond to different cold unfolders employed in the pre/hybridization reactions+ Two hybridization signals were detected by oligonucleotide a+ The characterization of the slower migrating band that corresponds to the tRNAsu ϩ precursor carrying the 39 trailer is reported in Buvoli et al+ (2000)+ This signal was not included in the calculation of the hybridization efficiency of oligonucleotide a+ Hybridization signals shown at the bottom of the figure correspond, from the left to the right, to the 88-nt-long in vitro-transcribed tRNAsu ϩ (2 ng), 10 mg of total RNA purified from untransfected cells, and 10 mg of total RNA purified from cells transfected with a plasmid carrying 16 copies of human serine suppressor tRNA gene, containing ;28 ng of the 85-nt-long RNAsu ϩ + Hybridization signals were normalized to the level of 5+8S rRNA and quantified as described in Materials and methods+ Hybridization efficiency is expressed as pixel counts+ A: Hybridization efficiency of oligonucleotide a measured in the presence of single unfolders+ B: Hybridization efficiency of oligonucleotide a measured in the presence of different combinations of unfolders+ the anticodon region contains unpaired bases that should allow an efficient oligonucleotide nucleation, it appears that productive heteroduplex formation is sterically inhibited by the unique structural characteristics of the anticodon stem (Mir & Southern, 1999)+ Our data suggest that the anticodon also maintains an inhibitory arrangement when the tRNA tertiary interactions are disrupted by unfolders targeting the T⌿C and the extra arms+ Thus, the separation of the anticodon stem strands appears to be an efficient way to promote heteroduplex formation+ When the tRNA secondary structures interfering with oligonucleotide a hybridization were completely eliminated, we observed the highest heteroduplex yield+ Interestingly, in this assay, a cooperative effect between unfolders was observed+ In fact, the hybridization signal detected in the presence of D2 and X1 was ;2+5-fold higher than expected for a simple additive effect of these unfolders+ This finding could reflect a more complex hybridization picture in which oligonucleotide a can play an active role in promoting the hybridization of one of the two unfolders with the formation of a more stable heteroduplex complex (for example: tRNA ϩ a ϩ D2 ϩ X1 R r tRNA/D2/a ϩ X1 r tRNA/D2/a /X1)+ This potential effect probably reduces the need for the use of long unfolders like TX+ Our results show that the presence of unfolders allows the use...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation